Polypharmacy in The Elderly (Turkey Health Literacy Journal, 2022)
Aging is a demographic situation that is becoming increasingly important for the whole world and our country. Factors such as the decrease in birth and death rate, the increase in modern medicinal facilities and the improvement of living conditions cause an increase in elderly population in the society. Being aware of the problems brought about by aging is important in determining the measures and corrective actions that can be taken in this regard. Increasing incidence of chronic diseases and various physiological changes occurring increase the possibility of problems in the drug use process. Pharmacokinetic and pharmacodynamic changes may cause an increase in drug-related sensitivity and a change in treatment effect. Polypharmacy is one of the leading drug-related problems in the elderly. Polypharmacy, which can be described as taking more than one drug at the same time, is a health problem that requires multidimensional thinking when its causes and consequences are considered. Consideration should be given in disease management, and the factors that alter the drug effect in olders should not be ignored while prescribing. Treatment approach that adopts the principles of rational drug use is the most effective way to prevent polypharmacy and to eliminate the problems it may cause.